Prevalence and Susceptibility Profile of E. Coli O157:H7 Isolated from Raw Milk in Kohat, Pakistan - Hakeem Zada, Amjad Ali Maitlo, Syed Zahoor Ul Hassan Zaidi, Komal Fatima, Mir Sadiq Shah, Malik Waleed Zeb Khan, Ghazala Shaheen, Tahira Shamim, Laila Sumreen, (Pakistan Journal of Medical & Health Sciences, 2022)
Diseases development due to food is a major threat to consumers; especially in countries where sanitation facilities are poor. E. coli O157:H7 strain causes major outbreaks among foodborne diseases. The current work investigated the prevalence of E. coli O157:H7 and their antibiogram profile in raw milk samples. A total of 180 samples were collected from milk shops in Kohat, Pakistan. The isolates were initially identified on colony morphology on different Media and later through biochemical tests. Isolates were also screened to differentiate E. coli O157:H7 from other fecal E. coli via sorbitol MaCconkey agar. Out of 180 samples 134 (74.4%) milk samples were positive for E. coli and 46 (25.6%) milk samples were negative. Antibiotic susceptibility test was performed by using antibiotics of different classes. Most of the isolates showed susceptibility to ciprofloxacin (82.5%) (80.4%), gentamicin (82.5%) (80.5%) and Oxytetracycline (85.5%) (85.6%) respectively and slightly resistant to Tetracycline (55.8%) (48.2%), Imepenam (52.6%) (42.8%), Ceftriaxone (45.5%) (40.6%), Trimethoprim (54.4%) (36.6%), Chloramphenicol (38.6%) (30.5%), and shows resistance to Amikacin (25.5%) (18.4%) and Cloxacillin (10.5%) (4.5%) respectively. The high frequency of E. coli O157:H7 in milk samples indicate poor hygiene during milking, transportation and milk storage. The awareness against spreading of this pathogen is necessary among stakeholders at different levels of milk handling.